Eosinophilic cellulitis (wells syndrome): a case report - Baabdullah, Ahmad Mohammad; Al Hawsawi, Khalid Ali; Alhubayshi, Bashayr Saad; Gammash, Marwa Rashed (International Journal of Research in Dermatology, 2021)
Eosinophilic Cellulitis is also known as Wells syndrome is uncommon dermatitis, characterized by the infiltration of eosinophils in the dermis. The exact etiology of the disease is unknown. Clinically, it is highly varied but commonly the presentation is pruritic erythematous plaque. We report a case of one and half years old healthy boy who developed itchy bullae on the dorsum of his hand with multiple erythematous papules over his extremities that started immediately after his vaccines. Histopathological examination of the lesion showed infiltrate eosinophils with typical flame figures. The case was successfully treated with corticosteroid course. This report aims to present a case of eosinophilic cellulitis (Wells syndrome) triggered by the vaccine with a literature review of the disease. In conclusion, atypical presentation of any inflammatory disorder or that not responding to appropriate treatment should trigger suspicion of eosinophilic cellulitis. Up to now, systemic corticosteroids are the most successful treatment of eosinophilic cellulitis.